Aspek Hukum Terhadap Jual-Beli Seks Toys Di Indonesia - Temongmere, Dominggus; Tuasikal, Hadi (Journal of Law Justice (JLJ), 2023)
This research aims to find out what legal aspects are against individuals or corporations who trade sex toys in Indonesia and their legality; to find out the application of criminal sanctions and fines against fines against individuals or corporations who trade sex toys in Indonesia as a business. The research used, through the Normative Juridical approach. The types of data used are primary data, namely data obtained from laws and regulations, secondary data, namely data obtained from literature studies (legal literature) and tertiary data, namely data obtained from legal dictionaries/ legal books/laws and regulations/large dictionaries of the Indonesian language. The results showed that; (1) Legal aspects of buying and selling sex toys in Indonesia. In fact, in legal facts there is not a single statutory regulation or special regulation that gives permission and (2)Application of Criminal Sanctions Against Perpetrators As Pornography Services Who Sell Sex Toys In Indonesia. To impose criminal sanctions for these acts, namely 'pornography services' as a result of unlawful acts, there are 4 (four) legal aspects that can be applied; the first is Article 1 number 2, Article 4 paragraph (1) letters d and e, Article 4 paragraph (2) letters a, b and d of Law No.44/2008 concerning Pornography, the second is Article 45 paragraph (1) of Law No.19/2016 concerning Electronic Information and Transactions (ITE), the third is Article 2.The results of the research show that; (1) Legal aspects of buying and selling sex toys in Indonesia. In fact, as a matter of legal fact, there is no single statutory regulation or special regulation that provides permission and (2) Application of Criminal Sanctions Against Perpetrators As Pornography Services Who Sell Sex Toys In Indonesia.To impose criminal sanctions for these acts, namely 'pornography services' as a result of unlawful acts, there are 4 (four) legal aspects that can be applied; the first is Article 1 number 2, Article 4 paragraph (1) letters d and e, Article 4 paragraph (2) letters a, b and d of Law No.44/2008 concerning Pornography, the second is Article 45 paragraph (1) of Law No.19/2016 concerning Electronic Information and Transactions (ITE), the third is Article 282 paragraph (1, 2 and 3) of the Criminal Code and the fourth is Article 533 numbers 1, 3 and 4 of the Criminal Code..